Autoethnography: narrative form of knowledge generation (Andamios, Revista de Investigación Social, 2012)
This article has a double purpose, on the one hand, to contribute to the spreading of a field of study within the qualitative research perspective, and a way of writing and presenting results, called autoethnography. To achieve this goal the origins and development of this area are reviewed for the last decade of the twentieth century and the first one of the new millennium, as well as the main components that characterize it. The Anglosaxon specialized literature is taken as the base for this review owing to the fact that autoethnography is scarcely practiced in Spanish speaking countries. On the other hand, it is also a main purpose to offer an example of this narrative subgenre. The topic of the personal story that it’s included towards the end of the article is historically and socially delimitated since it refers to a very specific moment that has been hardly dealt with: it focus on the experience of the arrival of the first television set, during the fifties, to middle class homes in Mexico City.
Keywords: Autoethnography; qualitative inquiry; personal narrative; television; Mexico City